2013
DOI: 10.1002/col.21768
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual uniformity in digital image representation and display

Abstract: Digital image representation is perceptually uniform if a small perturbation of a component value—such as the digital code value used to represent red, green, blue, or luminance—produces a change in light output at a display that is approximately equally perceptible across the range of that value. Most digital image coding systems—including sRGB (used in desktop graphics), BT.709 (used in high‐definition television, HD), Adobe RGB (1998) (used in graphics arts), and DCI P3 RGB (used in digital cinema)—represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…These three coefficients represent the intensity (luminance) perception of a standard observer trichromat human to light of the precise Rec. 709 [42] additive primary colors that are used in the definition of sRGB.…”
Section: Colorimetric Grayscale Conversionmentioning
confidence: 99%
“…These three coefficients represent the intensity (luminance) perception of a standard observer trichromat human to light of the precise Rec. 709 [42] additive primary colors that are used in the definition of sRGB.…”
Section: Colorimetric Grayscale Conversionmentioning
confidence: 99%
“…This means that a certain light power produces different luminous sensations depending on its wavelength. To take this into account, CIE defines the concept of luminance, which is proportional to optical power across the visible wavelengths, weighted according to a standardized spectral weighting that approximates the spectral sensitivity of normal human vision and expresses it of the following form: Y=kmfalse∫780 nm380 nmE|λV|λdλ where;…”
Section: The Sensory Action Of Lightmentioning
confidence: 99%
“…Nevertheless, we will use the relative luminance with values from “0” to “100.” Where “0” corresponds with black and “100” corresponds with a reference white. The reference white value for relative luminance is chosen to correspond roughly to the luminance of a near‐perfect diffuse reflector in the scene …”
Section: The Sensory Action Of Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital files do not display uniformly across varied consumer level electronic displays using sRGB colour space, so there are practical limitations in producing a digital version. 19 Each of the 10 plates displays a ring shaped tritan foreground on a neutral background. Each ring has a gap, so the target resembles the letter C with the gap oriented to one of the eight positions marked A to H. Spectrophotometric analysis showed that the dominant wavelengths of the foreground pigments cluster around 440 nanometres.…”
Section: Introductionmentioning
confidence: 99%